Pengaruh Kompetensi Terhadap Kinerja Karyawan Koperasi Unit Desa (KUD) Bersama Makmur Desa Srimulyo - Ita Tri Utami; Ade Irma Suryani; Nurdin Nurdin (J-MAS (Jurnal Manajemen dan Sains), 2020)
The purpose of this research is to determine the level of competency, performance and whether work competency has a significant effect on the performance of employees in KUD Bersama Makmur Desa Srimulyo. In this study, the authors took the hypothesis that competence has a significant effect on employee performance. Analysis tools are used to find out the level of competency, the level of employees using analysis about scale. To find out the competency of work to employee performance using a simple linear regression analysis. The calculation result with scale range analysis tool for employee competency level is 81. While the results of a simple linear regression analysis show the result of the influence of independent variables on dependent variables is large. From the results of scale range analysis and simple linear regression analysis, in accordance with the benchmark, for work competency is included in the category of good and competency has a significant effect on employee performance. Thus the hypothesis in this study is proven.